Beam guidance, focal position shifting and beam profile shaping in ultrashort pulsed laser materials processing - Bechtold, Peter; Zimmermann, Maik; Roth, Stephan; Alexeev, Ilya; Schmidt, Michael (Springer Verlag, 2016)
In ultrashort pulsed (USP) laser micro-processing several optical and optomechanical components are needed to enable the desired process. Besides the USP laser itself, systems to guide and focus the laser beam are mandatory in almost all applications. Furthermore beam profile shaping, e.g. the creation of top-hat or super-Gaussian beam profiles, results in beneficial effects for many applications, such as increased efficiency and superior quality. In this chapter an overview of both established and up-to-date technologies regarding beam guiding, focal position shifting and beam profile shaping will be presented. For beam guidance and focal position shifting comparable key parameters will be stated to enable easy comparability. As an outlook on probable future applications, both temporal and spatial polarization profile shaping will be presented.
CRIS-Team Scopus Importer:2023-03-07